2012
DOI: 10.1007/s00406-012-0342-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of seizure threshold in electroconvulsive therapy: a prospective study

Abstract: At the start and during the course of electroconvulsive therapy (ECT), estimation of the seizure threshold (ST) is useful in weighing the expected effectiveness against the risks of side effects. Therefore, this study explores clinical factors predicting initial ST (IST) and levels of ST during the ECT course. This prospective observational study included patients aged ≥18 years receiving ECT without contraindications for dose titration. At the first and every sixth consecutive ECT session, ST level was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 29 publications
7
57
1
3
Order By: Relevance
“…Our analysis did not reveal weight as a significant predictor of ST either. This is largely consistent with clinical ECT data (Boylan et al, 2000;Chung, 2006;van Waarde et al, 2013c), except for a small predictive power of body mass index on BL ECT ST in one study (Chung, 2006).…”
Section: Interindividual Threshold Variation and Stimulus Individualisupporting
confidence: 80%
See 3 more Smart Citations
“…Our analysis did not reveal weight as a significant predictor of ST either. This is largely consistent with clinical ECT data (Boylan et al, 2000;Chung, 2006;van Waarde et al, 2013c), except for a small predictive power of body mass index on BL ECT ST in one study (Chung, 2006).…”
Section: Interindividual Threshold Variation and Stimulus Individualisupporting
confidence: 80%
“…The ability of this MT to explain 63.1% of the ST variance in our study is notable as known predictors of conventionally titrated ST for a given electrode placement explain less than 40% of the variance (Boylan et al, 2000;Chung, 2006;Galvez et al, 2015;Sackeim et al, 1994;van Waarde et al, 2013c). The strong correlation between MT and amplitude-titrated ST supports the explanation that the interindividual ST variability is influenced by individual anatomical parameters that also affect the MT.…”
Section: Interindividual Threshold Variation and Stimulus Individualisupporting
confidence: 71%
See 2 more Smart Citations
“…Estimation of the seizure threshold is used in weighing effectiveness against the risk of side effects. In a prospective study, van Waarde et al [16] found higher age and bifrontotemporal electrode placement to be predictors for higher seizure threshold levels at different time points, which should be taken into account when selecting ECT dosage. With respect to treatment of affective disorders, new treatment strategies based on mechanisms of neuroplastic processes should be developed and lead to regeneration of disturbed brain function.…”
mentioning
confidence: 99%